Cruise CAGE-17-3 - Bünz, Stefan (CAGE – Centre for Arctic Gas Hydrate, Environment and Climate Report Series, 2023)
The overall goal of cruise CAGE 17-3 is to collect seismic, multibeam and water column data in an area along the northern flank of the Bear island trough and on the W-Svalbard margin. The objectives associated with the overall goal are to better understand the occurrence of gas hydrates and fluid leakage, the source of the gas in these systems, and seafloor expressions of fluid seepage. In order to address these objectives we plan to carry out: 2D and 3D P-Cable seismic and ocean-bottom seismic acquisition over a complex leakage and source-to-sink plumbing system in the Leirdjupet Fault complex in the SW Barents Sea;Recovery of one of CAGE’s ocean floor observatory from the crater area at the northern flank of the Bear Island Trough;Repeat of P-Cable 3D seismic acquisition on the eastern segment of the Vestnesa Ridge for time-lapse seismic studies of fluid flow and gas hydrates dynamics;2D multi-channel seismic for reconnaissance and stratigraphic correlation in the Molloy Ridge area;Multibeam mapping to fill in gaps and improve resolution of existing data using the upgraded EM302 system on R/V Helmer Hanssen The cruise may be known as: CAGE17_3